APLIKASI BISNIS MODEL KANVAS PADA PT. DWI ANEKA JAYA KEMASINDO, TANGERANG - Kuncoro Wibowo (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
PT. Dwi Aneka Jaya Kemasindo is a company that produces cardboard packaging as well as making paper and other things related to paper for packaging and other products. The research carried out there were several problems including the internal and external environmental situation, as well as existing threats including human resources caused by a workforce who was still working full time when the available factories were only 2 factory locations from the previous 3 factories available. The purpose of this paper is to contribute to company management in making strategic decisions about what products and services to develop. The author researching with Business Models Canvas, SWOT analysis, Pestle Analysis as an alternative to additional analysis covering aspects of human resources, external factors, internal factors and systems, as well as other aspects that are developed in an integrated and comprehensive manner. The results of this integrated management are expected to provide improvements and priority programs that must be implemented so that the company can avoid risks that will harm its survival.